Examining university students' satisfaction with online food delivery apps - Mohamed Noor, Illysia Isobel Miriam; Roslan, Muhammad Asyraful Hakim; Farook, Ferial; Ahmad, Roslizawati; Ismail, Anida (GADING (Online) Journal for Social Sciences, 2024)
Online food delivery (OFD) services have rapidly gained traction within Malaysia's food and beverage industry, reshaping traditional dining practices. This study explores the influence of visual design, navigation quality, information design, delivery service, timeliness, and security on the satisfaction of Universiti Teknologi MARA, Permatang Pauh students. Through a detailed analysis of design elements and their effects on user engagement and platform usage, the research aims to uncover how visual aesthetics impact user trust and preferences. Using stratified sampling, 200 valid responses were collected from students in the Science and Technology and Business and Management faculties. Applying the Technology Acceptance Model (TAM), the findings underscore the critical roles of perceived usefulness and behavioural control in determining students' intentions to use food delivery apps. The study provides valuable insights for enhancing OFD services within the higher education context.